THE ROLE OF POLITICAL DEVELOPMENT IN NATIONAL DEVELOPMENT: INDONESIA - Lestari, Sulistyani Eka (Universitas Nasional, 2020)
Political development in Indonesia with Pancasila democracy has experienced many challenges and obstacles. Indonesian culture which is strongly influenced by ethnic and religious interests must continue to adapt to the Pancasila democracy which is a nationalism nationalism. This condition since independence until now has experienced many positive changes, starting from the issue of central and regional conflicts and building the strength of national unity. The founders of the Indonesian people put them together in the form of Unity in Diversity as the ideological power of the nation. With a very large population, a big national problem, it requires political development in Indonesia that is directed, fair and wise.